2005
DOI: 10.1093/jac/dkh497
|View full text |Cite
|
Sign up to set email alerts
|

[13C]Methionine breath test: a novel method to detect antiretroviral drug-related mitochondrial toxicity

Abstract: The [(13)C]methionine breath test possibly showed mitochondrial impairment in antiretroviral-treated HIV-positive patients, particularly with hyperlactataemia. This non-invasive test can be used to monitor drug-related mitochondrial toxicity in vivo and to discover early and asymptomatic damage of the respiratory chain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…Methionine transamination is another potential pathway of methionine catabolism that results in the conversion of the methyl or carboxyl carbon to CO 2 and occurs primarily in the liver. However, this pathway does not occur under normal metabolic conditions in mammals (18,24).Each of the pathways, as noted earlier, produces CO 2 in the intermediary metabolism of methionine. By relying on the pathways of methionine degradation to CO 2 , previous studies suggest that a 13 C-labeled methionine ([ 13 C]-Met) breath test ([ 13 C]-MBT) could be used to evaluate the methionine oxidative capacity of the liver (9).…”
mentioning
confidence: 87%
“…Methionine transamination is another potential pathway of methionine catabolism that results in the conversion of the methyl or carboxyl carbon to CO 2 and occurs primarily in the liver. However, this pathway does not occur under normal metabolic conditions in mammals (18,24).Each of the pathways, as noted earlier, produces CO 2 in the intermediary metabolism of methionine. By relying on the pathways of methionine degradation to CO 2 , previous studies suggest that a 13 C-labeled methionine ([ 13 C]-Met) breath test ([ 13 C]-MBT) could be used to evaluate the methionine oxidative capacity of the liver (9).…”
mentioning
confidence: 87%
“…Rather than inferring metabolism paths from detailed genetic testing, the patient is given a benign surrogate that is isotopically labeled, and then, the metabolism pathway is directly monitored via an exhaled gas, typically 13 C-labeled CO 2 (Modak 2007). For example, cancer patients are treated with 13 C-labeled methionine to assess mitochondrial toxicity of antiretroviral drugs (Milazzo et al 2005), or with [ 13 C]-dextromethorphan to assess breast cancer therapy with tamoxifen (Opdam et al 2015 …”
Section: Isotopically Labeled Tracer Compoundsmentioning
confidence: 99%
“…[76][77][78] Flow cytometric techniques employ a cationic lipophilic fluorochrome with an affinity for mitochondria with high membrane potential. This method has the added advantage that circulating leukocyte subsets are easily separated and compared.…”
Section: Research History Of Nucleoside Reverse Transcriptase Inhibitmentioning
confidence: 99%
“…The authors concluded that hepatic mitochondrial dysfunction is drug related as opposed to HIV related and that the 13 C methionine breath test is superior to lactate measurement for detection of subclinical toxicity. 77 Paediatric HIV presents additional scenarios where children who do not contract HIV are exposed to ART, either in utero during maternal treatment, or perinatally during prevention of mother to child transmission (PMTCT) of HIV. In addition, most HIV-infected children are not ART naïve prior to initiation of therapy, and clinical mitochondrial dysfunction has been described in over 30% of perinatally infected children followed up longitudinally.…”
Section: Research History Of Nucleoside Reverse Transcriptase Inhibitmentioning
confidence: 99%